Keberadaan Kesenian Ludruk Rukun Trisno di Kabupaten Jember Tahun 1990-2018 - pradana, dewi retno putri; Suharto, Suharto (History Department, Faculty of Humanities, University of Jember, 2021)
This writing aims to discuss the problems (1) What’s the background of ludruk art di Jember Region until 1991? (2) How was the development of Rukun Trisno’s ludruk art until 1991? (3) How was the existence of Rukun Trisno’s ludruk art starting 1991-2018 in Jember Region? The method used in this study is the historical method which includes collecting sources, criticizing sources, interpretations, and writing history (historiography). The results of this writing are (1) ludruk art in Jember Region is a type of adaptation art from various regions ini East Java which then develops and adapts itself to cultural customs ini Jember Region. (2) At the beginning of its establishment in the period of the 1945s until 1991. Rukun Trisno’s ludruk art experienced a significant development, it was because Rukun Trisno’s ludruk art was one of the arts that carried Jember’s unique values so that it was close to the community. (3) In the period after the 1990’s the Rukun Trisno ludruk art began to experience a decrease in the intensity of the performance, this was due to the onslaught of modern entertainment which the shifted the position of the Rukun Trisno in the community. The situation then led to various efforts both from the Rukun Trisno ludruk group and the government to develop the elements of Rukun Trisno ludruk art to keep abreast of the times so that its existence was always accepted by the public.